Mecanização e intensificação do trabalho no corte de cana do CAI canavieiro do estado de São Paulo - Reis, Leonardo Ferreira (2012)
Assuming that the work is the central category in the production process, the relationship between the recent modernization, in special in the harvesting activities, and the manual harvesting work intensification were studied in the Sugarcane Agroindustrial Complex of São Paulo State. The work intensification, which involves high energy expenditure by the workers, is produced by a strong degradation of their life and work quality, in special as a result of the meritocracy system adopted for their payment, once it takes into account the sugar cane harvesting production per worker. The modernization of the Brazilian agriculture, that started in the 60`s, heavily influenced the manual work intensification. At that time, the Brazilian organization model encouraged an aggressive concentration of land and capital, and tried to suppress most of the social workers movements in rural areas. In the 90 s, the sugar and alcohol sectors presented a sharp increase, mainly due to the broad plan for implementing the use of biofuels, specially produced from sugarcane. A new process of modernization started in 2007, when an agri-environment protocol was signed up between sugar cane mills owners and the State of Sao Paulo government. Seeking to reduce the environmental and social liabilities of this sector, this protocol prescribes the end, by 2014, of the pre-harvesting sugarcane burning in areas where harvesting could be mechanized. The present study includes information from three sugarcane mills and from interviews with actors of the Agroindustrial Sugarcane Complex of São Paulo State to evaluate the consequences of sugarcane harvesting mechanization on manual harvesting labor intensification. Taking into account the harvesting costs, it was obtained a value of R$6.24/ton by using manual harvesting and R$3.41/ton to R$5.33/ton when harvesting was mechanized, taking into account 860 and 550 ton/day of harvested sugarcane. ..These results indicate a great economic advantage of the mechanized over the manual harvesting. Therefore, it was observed that mechanization did not attain the goals proposed by the agri-environment protocol. The sugarcane manual harvesting is still widely used to support the mechanization harvesting , which include areas of high slope and low machine accessability. Higher productivity areas are mechanized to obtain higher benefit/cost, leaving those of low productivity for manual harvesting. The comparison of the historical series data of the manual harvesting productivity between 2007/2008 and 2011/2012 indicates that sugarcane harvesting mechanization is responsible for the increase of labor work intensification, This increase in work intensification 10 is a consequence of the effort to attain about the same wage as before harvesting mechanization was implemented.